Evaluation of the Immune Response Induced by Coronavac 28-Day Schedule Vaccination in a Healthy Population Group - Sandino-Garcia, A; Imarai-Bahamonde, C; Acuna-Castillo, C; Valdes-Henriquez, D; Leiva-Salcedo, D; Barrera-Ávalos, C; Reyes-Lopez, F (Frontiers Media S.A., 2022)
CoronaVac vaccine from Sinovac Life Science is currently being used in several countries. In Chile, the effectiveness of preventing hospitalization is higher than 80% with a vaccination schedule. However, to date, there are no data about immune response induction or specific memory. For this reason, we recruited 15 volunteers without previous suspected/diagnosed COVID-19 and with negative PCR over time to evaluate the immune response to CoronaVac 28 and 90 days after the second immunization (dpi). The CoronaVac administration induces total and neutralizing anti-spike antibodies in all vaccinated volunteers at 28 and 90 dpi. Furthermore, using ELISpot analysis to assay cellular immune responses against SARS-CoV-2 spike protein, we found an increase in IFN-gamma- and Granzyme B-producing cells in vaccinated volunteers at 28 and 90 dpi. Together, our results indicate that CoronaVac induces a robust humoral immune response and cellular immune memory of at least 90 dpi. Copyright © 2022 Escobar, Reyes-López, Acevedo, Alonso-Palomares, Valiente-Echeverría, Soto-Rifo, Portillo, Gatica, Flores, Nova-Lamperti, Barrera-Avalos, Bono, Vargas, Simon, Leiva-Salcedo, Vial, Hormazabal, Cortes, Valdés, Sandino, Imarai and Acuña-Castillo.